2007
DOI: 10.1016/j.bbamem.2007.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Modification of membranes by quercetin, a naturally occurring flavonoid, via its incorporation in the polar head group

Abstract: Quercetin is a naturally occurring flavonoid that has a lot of beneficial properties to human health. In this report, using the spin label technique, the influence of quercetin on the fluidity of multilamellar DPPC liposomes was studied. The polarity of the environment preferred by quercetin was also examined by determining the dependence of the position of electronic absorption maxima on dielectric properties of different environments. Autofluorescence of quercetin was also used to examine its distribution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 33 publications
7
54
0
1
Order By: Relevance
“…Such effects were found for erythrocyte membrane proteins [12,13] and also for gramicidin ion channels [14].…”
Section: Accepted M Manuscriptmentioning
confidence: 80%
“…Such effects were found for erythrocyte membrane proteins [12,13] and also for gramicidin ion channels [14].…”
Section: Accepted M Manuscriptmentioning
confidence: 80%
“…They also suggested that flavonoids with more hydroxyl groups have stronger interaction with DPPC membrane interface and that binding of more hydrophilic flavonoids occurs with increasing pH at the membrane surface. Translocation of QC in the polar part of the lipid bilayer, at physiological pH, may be correlated with its protective ability against different deleterious agents including radical scavenging activity (Ollila et al, 2002;Pawlikowska-Pawlega et al, 2007). Deprotonation generally enhances the antioxidant action of the hydroxyflavones due to decrease in IP and BDE upon deprotonation (Peytar-Maillard, Cuvelier, & Berset, 2003;Tyrakowska et al, 1999).…”
Section: Ph Dependent Synergism Between Lettuce Extract and Quercetinmentioning
confidence: 99%
“…For stability reasons and low leakage of encapsulates, it is now recommended and approved to use phospholipids with high saturation degree (Pawlikowska et al, 2007) and also by optionally adding cholesterol (Ionescu & Ganea, 2012), which increases membrane stiffness. As application of synthesized phospholipids or cholesterol is not appropriate in food applications, the use of mixed lecithins, e.g., soy lecithin, is cost efficient, unproblematic to food legislation and more nutritionally valuable (Laye, McClements, & Weiss, 2008).…”
Section: Introductionmentioning
confidence: 99%